The connection between trust and leadership styles in Slovene organizations - Jure Kovaéc; Manca Jesenko (Journal for East European Management Studies, 2010)
In leadership, trust between superiors and subordinates plays a very important role. This article presents the results of empirical research covering the connection between the level of trust within an organization and leadership styles, which were defined in a dichotomous way (democratic vs. nondemocratic). In order to understand the mutual connection between trust and leadership on a deeper level, we selected delegation, communication and control as important elements in the leadership process. The results obtained in the analyses indicate the connection between the level of democracy in leadership styles and the level of formalisation in delegation, communication and the control of the tasks of one's subordinates, as well as the democracy in leadership and the level of trust. – – Bei Führung spielt Vertrauen zwischen Vorgesetzten und Untergebenen eine wichtige Rolle. Der Artikel beschäftigt sich mit den Ergebnissen der empirischen Forschung bezüglich des Zusammenhangs zwischen dem Ausmaß an Vertrauen innerhalb von Organisationen und den Führungstypen, die in dichotomer Form definiert werden (demokratisch vs. nicht demokratisch). Um den wechselseitigen Zusammenhang zwischen Vertrauen und Führung besser verstehen zu können, wurden Delegation, Kommunikation und Kontrolle als wichtige Elemente des Führungsprozesses ausgewählt. Die Ergebnisse der Analyse zeigen einen Zusammenhang zwischen dem Ausmaß an demokratischer Führung und dem Formalisierungsgrad, der bei Delegation, Kommunikation und Kontrolle der Aufgaben von Untergebenen angewendet wurde, sowie einen Zusammenhang zwischen demokratischer Führung und Ausmaß an Vertrauen.
Keywords: 650; trust; organisation; leadership; leadership styles; conmmunication; delegating; control